Mobility for learners and staff – higher education students and staff mobility inter-institutional agreement 2014-15 – 2020-21 between programme countries Università IUAV di Venezia and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate for exchange of students and/or staff in the context of the Erasmus + programme. - Subject area: Art and design; Architecture